On Modelling of Geomechanical Behavior of Supported Rock Mass in the Vicinity of Underground Structures - Michael A. Zhuravkov; Siarhei N. Lapatsin; Kirill A. Ripka (Механика машин, механизмов и материалов, 2022)
The paper presents a method of modelling the mechanical behavior of supported rock mass, in the vicinity of complex underground structures. The method is based on calculations of the effective mechanical properties of the bolted rock mass. The algorithm is based on the effective properties of a bolted rock unit that are obtained by conducting a series of numerical experiments. These experiments allow to define the values of correction factors, which, in turn, determine the difference in mechanical behavior of supported and non-supported rock mass. Such approach makes it possible to calculate the stress-strain state of complex space underground structures precisely without direct considering of the roof bolting elements. The application of the proposed method is demonstrated on the example of an applied problem of the strength assessment of geotechnical system “underground equipment chamber — enclosing potash rock mass”. The results of the research have a wide range of applications since they can significantly simplify and speed up the process of strength and stability calculations of bolted underground structures and make the results more accurate.